ANALISIS SISTEM VIDEO DAN AUDIO FLOW PADA STUDIO NEWS DI PT. LATIVI MEDIAKARYA (tvOne) JAKARTA - , PRINNESTY TALENTA NABABAN, Nur Sulistyawati, S.T., M.T. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Serving news is presented every television station greatly affect the interest of the television audience, especially in the presentation of news that is always updated, fast and reliable. One of the challenges in the presentation of news broadcasting is done live broadcasts from within the studio itself or from outside, and how all the crew involved can work together to process audio video studio can produce a smorgasbord of exciting news, both in terms of video quality is good and the resulting sound is also good. Any good studio news studio and studio audio video entertainment has a different flow. The study focused on the audio video news flow for the studio that has a high level of complexity. Video processing in the studio using multikamera system. Centralized process that occurs in the input and output all audio devices that are connected and amplification - signal amplification to get the best results, as well as with the cable numbering code, can facilitate the tracking every input and output that goes out. Video processing results will be as a PGM output of the switcher and as a backup, PGM from going into the routing switcher and output switcher Remote - 4 PGM are ready to be executed. For audio, the output end of a Main Out L and R Main Out which will be transmitted with Fiber Optics.